Labor Market Dynamics in Developing Countries : Comparative Analysis using Continuous Time Markov Processes - Bosch, Mariano; Maloney, William (World Bank, Washington, DC, 2012)
The authors study the dynamics of three developing country labor markets using recent advances in the estimation of continuous time Markov processes. They first examine the flows of workers among five states: three types of paid labor, unemployment, and out of the labor force. The authors find a high degree of commonality in patterns of worker flows among the three countries and attempt to compare the flexibility of the markets by examining an index of overall mobility. Second, they seek to establish whether the issues of advanced country labor markets apply to developing country markets or whether the latter constitute a different phylum. Paralleling the mainstream literature on the role of being out of the labor force as discouraged unemployment, the authors then identify some common stylized facts about the role of the informal self-employed and salaried sectors and to what degree they serve as a holding pattern versus a desirable alternative to formal sector work. In the process, the authors identify very strong differences in mobility patterns between men and women and attempt to shed some light on whether these differences arise from discrimination or perhaps instead the constraints imposed by household responsibilities. Finally, they study labor market adjustment across the business cycle in Mexico and identify patterns of job creation and destruction among the three paid sectors and confirm the mainstream view of the role of out of the labor force as a procyclical phenomenon.